Estimation of hepatitis B–positive rates in Chinese blood donors by combining predonation and postdonation screening results. Issue 5 (13th February 2019) - Gao, Zhan; Liu, Jing; Fu, Ping; Huang, Mei; Cao, Ru'an; Wen, Xiuqiong; Zhang, Chunhong; He, Tao; Mao, Wei; Liao, Dan; Ke, Ling; Yang, Yashan; et al.
Abstract: Background: Chinese blood centers use Hepatitis B surface antigen (HBsAg) rapid test (RT) in pre‐donation and two rounds of screening with different enzyme‐linked immunosorbent assays in post‐donation. Nucleic acid testing (NAT) on screening non‐reactive (SC‐) donations has been gradually implemented since 2010. Yet RT+ and SC‐/NAT+ donors are seldom included in hepatitis B virus (HBV) positive rate estimates in Chinese blood donors. Methods: We performed HBsAg neutralization test (NT) on whole blood (WB) with pre‐donation RT+ results and post‐donation screening reactive (SC+) samples from Mianyang and Chongqing in 2015. The annual totals of pre‐ and post‐donation NT+ donors were combined with the annual totals of SC‐/NAT+ donors to derive the estimated HBV positive rates. Result: In Mianyang and Chongqing, 59.4% and 68.2% of RT+ donors in Jan‐Aug 2015 contributed for NT, 95.5% and 97.2% of which were NT+ respectively. In 2015, 422 and 667 donors from Mianyang and Chongqing respectively were HBsAg RT+, yielding estimated 403 and 648 pre‐donation RT+/NT+ deferrals. 411 and 668 post‐donation SC+ samples were NT tested from Mianyang and Chongqing, of which 249 and 323 were NT+ respectively. An estimated 63 donors in Mianyang and 88 donors in Chongqing were SC‐/NAT+. The estimated HBV confirmed positive rate in blood donors are 1.59% in Mianyang and 1.01% in Chongqing. Conclusion: Pre‐donation HBsAg RT effectively intercepts donations from HBV infected donors. Using NT confirmatory results from RT+, SC+ and SC‐/NAT+ donors, this study provides a model for more accurate estimation for HBV positive rates in China.